Auto tagging of facial images for digital photo albums - Lim, Chu Xiang. (2013)
With the constantly improving technology, taking images of yourself or with a group of friends and storing the images can be done anywhere by just using personal mobile phones. With such convenience, hundreds or thousands of images can be taken and uploaded to popular social network websites such as Facebook and Twitter every day. But, tagging of names to every one in every single image becomes a hassle and requires a long time every time the user uploads images to his/her personal album. Through this project, the student aims to automatically tag the name(s) of any individual in his/her digital photo albums.